2019
DOI: 10.1177/1049731519867432
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Issues in Functional Family Therapy: A Narrative Analysis of the Evidence

Abstract: This analysis of functional family therapy (FFT) studies examines whether their variable outcomes are attributable to implementation issues. Studies were identified firstly, by way of a recent overview, supplemented by an update of a highly sensitive search including 15 databases, 10 websites, all existing relevant reviews, gray literature as well as contacting experts in the field. Updated searches were conducted in August 2018 and were analyzed according to the Oxford Implementation Index and an assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Littell (2005Littell ( , 2006 questions the quality of the evidence for MST in a number of respects and notes that much of it has been generated by the developers. Weisman and Montgomery (2020), in their meta-analysis of FFT, found that half of the studies were authored by FFT developers, and there was a marked difference between the results of their studies (all found positive effects) and the independent studies (all but one found null effects). Other authors report difficulties for FFT with engagement.…”
Section: Evidence-based Practices For Complex Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Littell (2005Littell ( , 2006 questions the quality of the evidence for MST in a number of respects and notes that much of it has been generated by the developers. Weisman and Montgomery (2020), in their meta-analysis of FFT, found that half of the studies were authored by FFT developers, and there was a marked difference between the results of their studies (all found positive effects) and the independent studies (all but one found null effects). Other authors report difficulties for FFT with engagement.…”
Section: Evidence-based Practices For Complex Traumamentioning
confidence: 99%
“…A UK study (Humayun et al, 2017) cited a 40% dropout rate amongst offending and anti‐social youth. Other researchers cite a lack of evidence with working class, non‐White and high‐risk young people (Darnell & Schular, 2015; Weisman & Montgomery, 2020). A report by the Early Intervention Foundation (2019) summarised mixed results for FFT and highlighted a lack of long‐term evidence and incorporation of dropout data into the evidence.…”
Section: Introductionmentioning
confidence: 99%
“…None of these have examined the factors and elements of RSIs’ implementation that stakeholders experience as challenging. This is concerning in light of the potential impact of implementation quality on child and family outcomes (Powell et al, 2014; Weisman & Montgomery, 2020) and many known obstacles faced by nongovernment organizations when implementing RSIs, including human and financial resource limitations, differences in organizational culture, and a lack of support available to progress an implementation (Bach-Mortensen et al, 2018).…”
Section: The Australian Rsi Experiencementioning
confidence: 99%